(untitled) (International Journal of Engineering and Computer Science, 2015)
-Denial of Service (DoS) attack is presently a very serious threat for the Internet security. These attacks attempts to exhaust victim’s resources e.g. CPU cycles, memory or network bandwidth. Thus disturb the consistent access of services to the user. When DoS attacks are formed by multiple distributed computer it is called as distributed denial of service (DDoS) attack. DDoS attacks can weaken computing and communication power of its victim within a short period of time. Because of seriousness of the problem many defense mechanisms have been proposed to encounter the attack. In this paper, two types of techniques for DDoS attacks and their countermeasure are given so that a better understanding of attack can be achieved